Anchor Movement Strategy for Conjecture Geometry Based Localization Scheme in Wireless Sensor Network - Niraj Bhupal Kapase; Santosh P Salgar; Mahesh K Patil; Prashant P Zirmite (Institute of Advanced Engineering and Science, 2016)
Abstract—Localization of sensor node with least error is one of the major concern in wireless sensor network as some of the application require sensor node to know their location with high degree of precision. For mobile anchor based localization many of the path planning schemes already developed which includes scan, double scan, Circles & S- Curves. These path planning schemes have some limitations like localization error, Number of sensor nodes covered in the network, Trajectory length of mobile anchor node. This paper represents anchor movement strategy which is based on Scan path, with modifications are made in such a way that it satisfies the requirements of localization scheme. This movement strategy ensures that trajectory of mobile anchor node will minimize localization error and also will cover majority of sensor node in the environment. The localization error yielded by Modified Scan algorithm is in the range of 0.2 to 0.4m which is quite lower than the other existing mentioned path planning strategies producing localization error in the range 0.6 to 1.8mKeywords—Localization; Mobile anchor node; Wireless sensor network; Modified Scan algorithm